Korelasi antara kekuatan otot lengan, koordinasi mata-tangan, dan kemampuan servis atas pada pemain bola voli di Universitas Lampung. - Prayitno, Adi; Wicaksono, Lungit; Jaya Sumantri, Riyan; Siswoyo, Joan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study seeks to examine the correlation between arm muscular power, hand–eye coordination, and overhand serve performance among participants of the Volleyball Student Activity Unit at the University of Lampung. A quantitative correlational method was utilized, involving 15 male participants selected through purposive sampling. In this study, arm muscle power was evaluated using the two-hand medicine ball throw test, the ball throw-and-catch test for hand-eye coordination, and the AAHPERD test to assess overhand serve capability.  The Pearson Product–Moment correlation approach was employed for data analysis. The findings demonstrated a robust and statistically significant correlation between arm muscular strength (r = 0.807; p = 0.001) and hand–eye coordination (r = 0.908; p = 0.001) with overhand serve performance.  Upon simultaneous examination, both variables exhibited a robust connection (r = 0.759; p = 0.001), with hand–eye coordination demonstrating a more pronounced effect. The efficacy of the overhand serve is contingent upon the interplay of arm muscular strength and hand–eye coordination.  Consequently, volleyball training programs must prioritize muscular strengthening and coordination enhancement to maximize serving efficacy.